THE ROLE OF ONLINE REVIEWS IN SHAPING CONSUMER TRUST IN E-COMMERCE - Ismailova Khanifajon (Ecomind Press, 2025)
Online reviews have become an essential element in shaping consumer trust within the e-commerce landscape. As digital marketplaces lack traditional face-to-face interactions, consumers increasingly rely on peer-generated content to assess product quality, reliability, and seller credibility. This article explores how online reviews influence buying behavior, establish social proof, and contribute to or detract from brand trust. It also examines challenges such as fake reviews and strategies for ensuring authenticity. By understanding the psychological and technological factors behind online reviews, businesses can better manage their reputations and enhance consumer trust in competitive digital environments.
Keywords: Online reviews, e-commerce, consumer trust, digital marketing, social proof.